Agricultural aspects in river basin management plans - Fehér, János (Acta Agraria Debreceniensis, 2012)
In the European Region agriculture is the second largest water user after power industry cooling water use. As part of the implementation of Water Framework Directive EU Member States prepared their river basin management plans by the end of 2009 or first half of 2010, In these plans impacts of agriculture on water bodies have received attention. The detailed information elaborated in the plans by countries and river basin districts were uploaded into the WFD section of the WISE system. This database provides opportunity for multi-criteria analysis for different water types. The paper discusses the effects of agriculture on hydromorphological pressures and impacts affecting surface water bodies. It was pointed out that among the pressures affecting European surface water bodies the hydromorphological and diffuse pressures represent the highest ratios (Figure 1). Within the hydromorphological pressures affecting classified surface water bodies the ratio of pressures related to agricultural activities is low, it does not exceed 1% at European level. In case of Hungary the agriculture related river management pressures effect about 80% of the surface water bodies, which is much higher than the corresponding European average. The agricultural water abstractions affect about 10% of the Hungarian surface water bodies (Figures 2 and 3). The river and lake water bodies are impacted in significant ratio by nutrient enrichments and organic material enrichments, while in case of river water bodies the impact of organic material enrichments is also significant (Figures 4 and 5).